Obvladovanje neželenih dogodkov v zdravstveni negi v psihiatričnih bolnišnicah - Čuk, Vesna (Obzornik zdravstvene nege, 2010)
Introduction: An adverse event in nursing care is defined as an untoward, unintended, undesirable, and usually unanticipated event resulting in injury or complications, impairment of the patient's condition or compromised care that arise from health care management. It may also affect the overall qualityof care and safety of health care environment. Methods: The purpose of the study was to determine the incidence, prevalence and types of preventable adverse events in Slovenian psychiatric nursing care, and to examine and identify the extent to which organizing factors of inpatient psychiatric care environments are associated with the occurrence of these events. Results: The most common adverse events are falls and the patients' aggressive behaviour, directed towards themselves, other patients and health care providers. Certainadverse events are also generated by the nursing personnel. Discussion and conclusions: The study confirms that safety and quality in psychiatric care environments are related to the comportment of the nursing personnel. It has also been established that nurses' level of competence is not the principal contributory factor to the adverse events. The primary aim of the study is Co enhance the quality of care through a systematic research by monitoring, reporting and analysing the adverse events, and by the use of the spiral model of replication applicable in Slovene psychiatric care settings.
Keywords: Bolnišnice psihiatrične; Hospitals, Psychiatric; Kakovost zdravstvenega varstva; kvaliteta; Methods; neželeni dogodki; Nursing Process; Psihiatrična nega; Psychiatric Nursing; Quality Of Health Care; zdravstvena nega; Zdravstvena nega, proces; zdravstvene storitve